Pemanfaatan Situs Megalitik Selodiri Terjan untuk Pengembangan Materi Pembelajaran IPS pada Tingkat Sekolah Menengah Pertama - Abi Amar Zubair; Hasib Widya Azzahid; Risqi Gilang Maulana (ASANKA : Journal of Social Science and Education, 2024)
There are still teachers who teach social studies subjects that seem less varied, so that students feel bored and tired, and learning becomes less meaningful. This study aims to obtain information about how the Terjan Site can be used as a source of social studies learning at the junior high school level. This study uses a qualitative descriptive approach with a field research type. Interview, observation, and documentation study techniques are used in data collection. The results of the study show that the Terjan Site can be used as a source of social studies learning in class VII semester 1 through the field trip learning method contained in the social studies material on the theme of environmental diversity, sub-chapter of Habituation to Preserve the Environment, and material on human activities in prehistoric times in the Merdeka Curriculum. Utilization of the Terjan Site as an object of social studies learning can increase motivation, learning outcomes, creativity, nationalist character, environmental care, and critical thinking skills of students. In conclusion, the Terjan Site can be used as a source of social studies learning at the junior high school level, where the utilization of learning is adjusted to relevant material, namely in class VII semester 1. ABSTRAK Masih terdapat guru yang mengajar mata pelajaran IPS terkesan kurang bervariasi, sehingga peserta didik merasa jenuh, bosan, dan pembelajaran menjadi kurang bermakna. Penelitian ini bertujuan memperoleh informasi tentang bagaimana Situs Terjan dapat dijadikan sumber belajar IPS jenjang Sekolah Menengah Pertama. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan jenis penelitian lapangan. Teknik wawancara, observasi, dan studi dokumentasi digunakan dalam pengumpulan data. Hasil penelitian menunjukkan Situs Terjan dapat dijadikan sumber belajar IPS di kelas VII semester 1 melalui metode pembelajaran karyawisata yang terdapat pada materi IPS Tema Keberagaman Lingkungan Sekitar, Subbab Pembiasaan Diri untuk Melestarikan Lingkungan, materi Aktivitas Manusia Zaman Praaksara pada Kurikulum Merdeka. Pemanfaatan Situs Terjan sebagai objek pembelajaran IPS dapat meningkatkan motivasi, hasil belajar, kreativitas, karakter nasionalis, peduli lingkungan, dan kemampuan berpikir kritis peserta didik. Kesimpulannya, Situs Terjan dapat digunakan sebagai sumber belajar IPS tingkat SMP dimana pemanfaatan pembelajaran disesuaikan dengan materi relevan yakni terdapat pada kelas VII semester 1.